SCAFFOLDING MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DALAM PEMBELAJARAN MATEMATIKA - Purna Bayu Nugroho (Universitas Muhammadiyah Kotabumi, 2017)
Critical thinking is the ability should be owned by the students. However, the facts shows that critical thinking which found is still low. It can be seen from the quality of questions and answers in the process of teaching and learning. Scaffolding is one of learnings which can imrpove students’ critical thinking in mathematic subject. Scaffolding consist of environtment provisions, explaining, reviewing dan restructuring, also development conceptual thinking. There are several scaffolding technique which can be used; (1) modeling of desired behaviors, offering explanations, inviting student participation, verifying and clarifying student understandings, inviting students to contribute clues; (2) scaffolding which emphasize on the use of socratic and open-ended questions.